2009
DOI: 10.1111/j.1399-3046.2009.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and health related quality of life in children following kidney transplantation

Abstract: Participation in PA is often diminished in children with CKD. Limited research exists on exercise tolerance/capacity but no studies to date have investigated lifestyle PA and its determinants in these children. The aim of this study was to investigate level of PA and potential physiological and psychological associations in a group of pediatric KTx recipients compared with CS. Twenty KTx and 33 CS participated. PA was measured by PAQ. HRQOL (PedsQL 4.0) and CY-PSPP were also measured. BMI and WC was recorded i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 36 publications
5
34
1
4
Order By: Relevance
“…Low levels of physical activity were linearly associated with physical performance and self-reported health-related quality of life after adjustment for age, sex, and BMI. Our results agree with the findings of Hamiwka et al (10), who reported that 20 pediatric kidney transplant recipients took an average of 9282 daily steps. Our results extend those by including children with other stages of CKD; evaluating correlates of physical activity in these children; and addressing the associations among limited physical activity, poor physical performance, and deficits in physical functioning.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Low levels of physical activity were linearly associated with physical performance and self-reported health-related quality of life after adjustment for age, sex, and BMI. Our results agree with the findings of Hamiwka et al (10), who reported that 20 pediatric kidney transplant recipients took an average of 9282 daily steps. Our results extend those by including children with other stages of CKD; evaluating correlates of physical activity in these children; and addressing the associations among limited physical activity, poor physical performance, and deficits in physical functioning.…”
Section: Discussionsupporting
confidence: 83%
“…There has been a worldwide decline in aerobic fitness levels and physical activity (5) among children, with a corresponding increasing prevalence of overweight and obese children and young adults (6,7). A few studies have shown that kidney transplant recipients are less active and have lower exercise capacity than healthy children, and that positive physical self-perceptions may be related to increased physical activity (8)(9)(10)(11). However, to our knowledge no studies to date have examined physical activity, physical performance, and physical functioning at the same time in children with CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Following the results of our previous publication [9] that showed low levels of PA in PTx patients as measured by pedometers, this study used accelerometry to further our understanding of PA of PTx patients in their daily lives and natural settings. In addition, gold standard physiological methods were used to measure exercise capacity and were supported by field testing.…”
Section: Discussionmentioning
confidence: 97%
“…As the lifespan of children and youth with chronic kidney disease (CKD) increases due to the benefits of successful transplant methods, healthy lifestyle choices, including the adoption of physical activity (PA), into daily life becomes an area for further investigation. A previous publication from our center reported reduced lifestyle PA over a 7-day period using pedometers when compared with healthy controls [9]. Pedometers provided an inexpensive measure of PA but were unable to assess activity intensity, frequency, and duration.…”
Section: Introductionmentioning
confidence: 96%
“…utilization, return to work in adults, and cognitive development and growth in children, successful kidney transplantation is the superior treatment modality for end-stage kidney disease (33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%